8-Formylophiopogonanone B Antagonizes Paraquat-Induced Hepatotoxicity by Suppressing Oxidative Stress - Qian, Jing-yu; Deng, Ping; Liang, Yi-dan; Pang, Li; Wu, Li-chuan; Yang, Ling-ling; Zhou, Zhouv; Yu, Zheng-ping (Frontiers in Pharmacology, 2019)
Flavonoids are some of the most important natural products with a variety of physiological activities. 8-formylophiopogonanone B (8-FOB) is a naturally existing homoisoflavonoid in Ophiopogon japonicus. Paraquat (PQ) has been widely used as a potent herbicide and has high toxicity in humans. The goal of the present study was to investigate whether 8-FOB could protect against PQ-induced hepatotoxicity in vitro and in vivo. We first tested the protective effects of 8-FOB on PQ-induced cytotoxicity in L02 cells by determining cell viability, intracellular oxidative stress levels, mitochondrial function and apoptosis in vitro. To verify the protective effects of 8-FOB, we pretreated mice with 8-FOB and assessed liver function, hepatic oxidative stress and histopathological changes after PQ administration. Our results revealed that 8-FOB could antagonize PQ-induced hepatotoxicity in vitro and in vivo. The antagonistic effects could be attributed to suppressing oxidative stress, preserving mitochondrial function, and inhibiting apoptosis. The present study is the first to document that 8-FOB, a homoisoflavonoid compound, is an effective antioxidant for antagonizing PQ-induced hepatotoxicity.